Rancang Bangun Aplikasi Kesehatan Mental Untuk Remaja Di Indonesia Berbasis Android - Dissa Aulia; Khanun Roisatul Ummah (Jurnal Media Computer Science, 2026)
Specialized treatment is essential to address the mental health challenges faced by Indonesian adolescents. Adolescents are often reluctant to seek professional help due to societal expectations, the transition from childhood to adulthood, and negative perceptions of mental health issues. The results of the 2022 I-NAMHS survey show that 34.9% of Indonesian adolescents experience symptoms of mental disorders, and 5.5% experience severe mental illness. To address this issue, an Android-based mental health solution information system called “Rileksin” has been developed. This application provides key features such as a user Mood tracker, relaxation music, breathing relaxation, positive visualization relaxation, stretching relaxation, articles, journaling , and a mission and reward system to increase user engagement. The “Rileksin” app offers safe and anonymous mental health support through Android devices. The system was developed using Android Studio with a database created on Firebase. For teenagers, this application provides meditation tools and direct access to information about mental health. The “Rileksin” application uses the waterfall system development method, which consists of the following stages: requirements analysis, system design, implementation, testing, evaluation, and maintenance. Based on the results of testing using the Black Box Testing method on the Relaksin app, it can be concluded that all the main features are working well and in accordance with the specified requirements. In addition, usability testing using the System Usability Scale (SUS) method obtained an average score of 83, which indicates that the app is in the excellent category and is easy to use for users.